Comparative Study of Premature and Older Adult Onset Coronary Artery Disease among Bangladesh Air Force Members (Journal of Armed Forces Medical College, Bangladesh, 2025)
Background: Coronary artery disease (CAD) is a major cause of morbidity and mortality worldwide. It is a disease usually found in the old age. Nowadays, however, it’s often suffered by young adults. Recently, it has been observed that a good number of young Bangladesh Air Force (BAF) members reported with the features of CAD and some of them presented in a very critical condition.Objective: To evaluate the pattern, various predisposing factors of CAD among the BAF officers as well as other members.Methods: This study was conducted by the patient data obtained from different bases of BAF for the period from 01 July 2022 to 30 Jun 2023. Total 67 serving male CAD patients were included in this study. Data were analyzed for the evaluation of premature coronary artery disease (PCAD) as well as older adult onset coronary artery disease (OCAD). PCAD was considered when age of onset was below 45 years and OCAD when age of onset was more than 45 years. Associated risk factors for CAD were also analyzed separately for PCAD and OCAD.Results: Out of total 67 coronary artery disease patients, 39(58.21%) had premature onset of coronary artery disease and 28(41.79%) had older adult onset coronary artery disease. Mean ages of PCAD and OCAD were 37.83 ± 5.25 and 53 ± 05 years respectively. Smoking habit (20.90%) and family history of premature CAD (17.91%) were significantly associated with PCAD. Other associated risk factors were hypertension, diabetes mellitus and dyslipidemia.Conclusion: Prevalence of PCAD among BAF uniform personnel is higher in comparison to older adult onset CAD. Positive family history of CAD and smoking habit were found to be significantly associated with the existence of PCAD. Focusing on primary prevention and optimal control of all CAD risk factors is necessary.JAFMC Bangladesh, Vol 20, No 2 (December) 2024: 08-10